2017
DOI: 10.1136/bcr-2017-221536
|View full text |Cite
|
Sign up to set email alerts
|

Filarial breast lump

Abstract: Lymphatic filariasis is one of the most debilitating and disfiguring scourges among all diseases. This report presents a case of a woman with recurrent breast nodularity after being previously operated for a suspected breast neoplasm. We would like to highlight the issue of similar clinical presentation of a filarial breast lump and other breast lesions leading to inappropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Ziehl-Neelsen staining, culture or PCR can be used for establishing the diagnosis 59 60. Other unusual pathogens that can cause granulomatous mastitis include Bartonella henselae 61 62, atypical mycobacteria,63–65 Actinomyces ,66 Brucella ,67 fungi68 69 and parasites 70–73. These unusual infections may be the initial presentation of HIV infection 74…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Ziehl-Neelsen staining, culture or PCR can be used for establishing the diagnosis 59 60. Other unusual pathogens that can cause granulomatous mastitis include Bartonella henselae 61 62, atypical mycobacteria,63–65 Actinomyces ,66 Brucella ,67 fungi68 69 and parasites 70–73. These unusual infections may be the initial presentation of HIV infection 74…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Patients with breast filariasis can present with a variety of clinical manifestations, ranging from asymptomatic to a breast lump which mimics inflammatory breast cancer [ 14 ]. A few case reports have shown that breast filariasis is mostly caused by Wuchereria bancrofti [ [4] , [5] , [6] , 14 ]. The most common site of breast filariasis is the upper outer quadrant of the breast, and the lesion seldom invades the ductal part [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presentation of breast filariasis is rare and may be misdiagnosed as a breast tumor or cyst [ 3 ]. The majority of the reported cases have been from India, which is an endemic area of lymphatic filariasis [ [4] , [5] , [6] ]. Extralymphatic presentations of filariasis have also been caused by zoonotic filaria [ 3 ].…”
Section: Introductionmentioning
confidence: 99%